Limites e possibilidades na educação de jovens e adultos: um estudo em escolas municipais e estaduais de Belém do Pará - PANTOJA, Pedro Correa (2020)
This study aims to identify the limits and teaching possibilities of action in the context of Adult Education in Belém-PA schools. In this context, it carried out a literature review in the light of authors such as Oliveira (1999), Perrenoud (2003), Charlot (2000), Campbell (2001), among others, who helped in the analysis of the different conceptions of the limits and possibilities of acting professor of Adult Education. Thus, it was found that the pedagogical Adult Education of teaching practice arises as a condition to restructure the relationship between knowing and doing this in the curricula of the Adult Education. The interaction, which is a key element of human development comes in the educational setting as the reference responsible for the innovation of education, basing pedagogical actions and renewing teaching practices. The results of the research show the limitations and Adult Education teacher possibilities simultaneously. On the one hand, the teacher is seen generally as a concerned researcher in promoting learning to work the imagination and creativity of the student, the basis for the formation of a thinking citizen and builder of your reality. On the other hand, the continuing education for this mode, which becomes evident in the relationship between teaching and learning, as school focused on Adult Education, therefore, is both a culture clash site and, like any situation of social interaction, a meeting place of singularities.